Counseling gifted students a guide for school counselors - Wood, Susannah M.; Peterson, Jean Sunde 1941- (New York Springer Publishing Company, LLC, 2018)
"Counseling Gifted and Talented Students in Schools is a complete handbook for understanding and meeting the needs of gifted students. Combining conceptual foundation, research, and relatable vignettes, Drs. Peterson and Wood teach us everything we need to know about creating gifted programs, identify gifted students, collaborating with educators, and equally if not more critical, understanding the unique developmental needs of gifted students. This book gets to the essence of the "whole" gifted student and how critical it is to not only foster intellectual and academic growth, but health identity developmental and mental well-being." -- Dan Peters, Ph. - D; Licensed Psychologist; Co-founder/Executive Director, SUMMIT CENTER Goes beyond academic considerations to address career development and social/emotional concerns - Created to fill a gap in both counselor education and gifted education, this is the only up-to-date text to provide a concise and practical overview of counseling services designed specifically for gifted and talented students. Grounded in the American School Counselor Association (ASCA) National Model for counseling programs, the book illuminates specific knowledge, awareness, and skills school counselors need to address concerns related not only to academics, but also to social and emotional development of this population. - The text delivers a theoretical and practical overview of gifted and talented education in the US and the responsibilities of school counselors as they pertain to this unique population. Going well beyond the common call to provide academic challenge, the book considers special characteristics of gifted and talented students as it examines the complexities of career development, college readiness, and concerns related to social/emotional development. It discusses how counselors can advocate for gifted students, lead efforts to match programming and needs, and collaborate with school staff and families. Vignettes depicting critical incidents and epitomizing needs are used to illuminate differentiated counseling approaches that support this student population. Each chapter highlights a key concept, and curriculum guidelines and resources for professional development support the text. - Key Features: Interweaves school counseling and gifted education research and practice - Considers characteristics and counseling concerns associated with giftedness Is based on the ASCA model for counseling programs - Examines the complexities of career development, college readiness, and social/emotional development in this population - Highlights key concepts and includes vignettes of critical incidents."-- Provided by publisher.
Counseling Gifted and Talented Students / Susannah M. Wood and Jean Sunde Peterson -- Aligning Service to Gifted Students With the ASCA National Model / Susannah M. Wood -- Characteristics and Concerns of Gifted Students / Jean Sunde Peterson -- Diverse Gifted Students: Intersectionality of Cultures / Renae D. Mayes, SaDohl Goldsmith Jones, and Erik M. Hines -- Theories That Support Programs and Services in Schools / Jean Sunde Peterson -- Identifying Gifted and Talented Learners in Schools: Common Practices and Best Practices / Tamra Stambaugh and Susannah M. Wood -- Working With Classrooms and Small Groups / Jean Sunde Peterson -- Academic Advising and Career Planning for Gifted and Talented Students / Michelle Muratori and Carol Klose Smith -- Personal/Social Counseling and Mental Health Concerns / Jean Sunde Peterson -- Collaboration, Consultation, and Systemic Change: Creating a Supportive School Climate for Gifted Students / Susannah M. Wood -- Empowering Parents of Gifted Students / Susannah M. Wood and Carrie Lynn Bailey -- School Counselors as Leaders and Advocates for Gifted Students / Susannah M. Wood, Erin M. D. Lane, and Matthew J. Beck -- Concluding Thoughts / Jean Sunde Peterson -- Appendix: Resources by Topic and Type.
Includes bibliographical references and index.
Keywords: Gifted children -- Education -- United States; Gifted children -- Counseling of -- United States; Educational counseling -- United States